Studi Sifat Fisika Tanah Gambut pada Kebun Karet dan Kelapa Sawit Rakyat di Kecamatan Rasau Jaya Kabupaten Kubu Raya - Gumilar, Tri; Junaidi, Junaidi; Suryadi, Urai Edi (Perkebunan dan Lahan Tropika, 2023)
This study aims to study the differences in the physical properties of peat soils in rubber and oil palm plantations in Rasau Jaya III Village Rasau District Kubu Raya District. The parameters of this study are, peat depth, peat maturity, measurement of ground water level depth, content weight, water content capacity field, total porosity, permeability, and some chemical properties, peat soil in people's rubber and oil palm plantations in Rasau Jaya District, Kubu Raya Regency.  Measurement of peat depth is taken up to the mineral soil boundary, has a 74 cm rubber peat depth and 66 cm oil palm. The level of maturity of both fields at the sapric level. The water resistant surface on rubber land is 70 cm and oil palm land is 58.8 cm. Average bulk density of depth 0 "“ 30 cm rubber land 0.34 g/cm3, palm 0.31 g/cm3. Depth 30-60 cm rubber 0.28 g/cm3, palm 0.38 g/cm3. Average field water capacity depth of 0-30 rubber fields 74, 63% palm 85.19%. While at a depth of 30-60 cm rubber land has 71.58% oil palm area of 84.58% vol. The average porosity of total soil depth of 0-30 cm palm oil is 86.96% higher than rubber area 82.37%. The average total porosity of soil at a depth of 30-60 cm is lower oil palm 81.82% rubber land 86.82% and both lands are classified as very porous criteria. The mean permeability values based on the t-test results were not significantly different.